2021
DOI: 10.1016/j.isci.2021.102108
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lidocaine alleviates postherpetic neuralgia in rats via regulation of neuroinflammation of microglia and astrocytes

Abstract: This study aimed to explore the effects and possible mechanisms of intravenous lidocaine in postherpetic neuralgia (PHN) rats. Mechanical withdrawal thresholds and thermal withdrawal latencies were measured. Open field test, elevated plus maze test, and tail suspension test were used to assess anxiety-and depressivelike behaviors. Microglia and astrocytes in spinal dorsal horn (SDH), prefrontal cortex (PFC), anterior cingulate cortex (ACC), and hippocampus were analyzed. The expression of TNF-a, IL-1b, and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…It is suggested that LC:SC activation reduces the production of pro-inflammatory cytokines by inhibiting glial cell activation. It is widely reported that occurrence of NP is often accompanied by the activation of glial cells, and the activated glial cells can release various pro-inflammatory cytokines (such as TNF-α, IL-1β, and IL-6), anti-inflammatory cytokines (such as IL-4, Arg1, and IL-10), and various analgesic and pain-causing substances [ 54 , 55 ]. The pro-inflammatory glial mediators regulate excitatory and inhibitory synaptic transmission in the spinal cord by enhancing nociceptive neurotransmission, which ultimately leads to central sensitization [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that LC:SC activation reduces the production of pro-inflammatory cytokines by inhibiting glial cell activation. It is widely reported that occurrence of NP is often accompanied by the activation of glial cells, and the activated glial cells can release various pro-inflammatory cytokines (such as TNF-α, IL-1β, and IL-6), anti-inflammatory cytokines (such as IL-4, Arg1, and IL-10), and various analgesic and pain-causing substances [ 54 , 55 ]. The pro-inflammatory glial mediators regulate excitatory and inhibitory synaptic transmission in the spinal cord by enhancing nociceptive neurotransmission, which ultimately leads to central sensitization [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of pain recognition, multiple brain regions were activated at the same time, while the activation of microglia in the prefrontal cortex (PFC), the anterior cingulate cortex (ACC), 22 and the hippocampus 21,23 may be responsible for persistent neuropathic pain. The activated microglia promote the release of proinflammatory cytokines, induce neuroinflammation, and enhance long‐term noxious nerve signal transmission, leading to central pain sensitization, causing and aggravating neuropathic pain 20 . After peripheral nerve injury (PNI), TNF‐α can differentially regulate hippocampus and spinal cord synaptic plasticity through a microglia‐dependent mechanism 23 .…”
Section: Ne Regulates Inflammatory Activation Of Microgliamentioning
confidence: 99%
“…More evidence of functional magnetic resonance imaging studies in patients with postherpetic neuralgia (PHN) suggests that there are abnormal functional activities in the regions of the brain linked to anxiety and depression 41 . Most PHN patients also have anxiety and depression that may be related to the activation of microglia at the PFC, ACC, and hippocampus 20 . Negrete et al injected intra‐articular sodium iodoacetate in kappa opioid receptor knockout mice, predynorphin knockout mice, and wild‐type mice to induce osteoarthritis; the results showed that all mice had abnormal pain, and the activation of microglia in the spinal cord and lumbar showed a similar increase.…”
Section: Microglia Lc–noradrenergic System and Anxiety/depressionmentioning
confidence: 99%
“…Nevertheless, previous studies showed multivariate results of the cortex in PTSD models. In an early-life stress and herpes zoster pain model, microglia in the PFC is markedly activated ( Ma et al, 2021 ; Usui et al, 2021 ). Neuroinflammation originating from microglia in the medial PFC induced by chronic stress, leading to depressive-like behavior ( Kitaoka, 2022 ).…”
Section: Discussionmentioning
confidence: 99%